Rotablation of Heavily Calcified Left Main Stenosis and Aortic Valve Valvuloplasty Under ECMO Cardiopulmonary Support - Ajmi, Issameddine (JACC Case Rep, 2020)
High-risk coronary intervention involving the left main coronary artery represents an indication for mechanical circulatory support in hemodynamically unstable patients. Extracorporeal membrane oxygenation permits adequate hemodynamic stabilization and myocardial recovery from life-threatening pulmonary and cardiac failure. Our case report demonstrates the importance of choosing the correct method of hemodynamic support in different case scenarios. (Level of Difficulty: Advanced.)